Kontribusi Vegetasi Lantai pada Infiltrasi Air di Area Sekitar Mata air Mudal, Purwosari, Gunung Kidul, Yogyakarta - Sancayaningsih, Retno Peni; Saputra, Alanindra (Prosiding KPSDA, 2015)
Water is important natural resources for people and spring is one of clean natural water resources in the village. Indonesia has high rain fall, but water availability varies spacially and temporally. The change of land cover or ecosystem in spring catchment area or surroundings decreases water catchment capacity. Therefore it is necessary to conduct a study of floor vegetation contribution on rain-water infiltration. This study aims to determine the structures and the roles of floor vegetation in regards of water infiltration at various degrees of slope. This study was carried out in two times, end of the dry season from June to October 2013 and end of wet season from March to June 2014. Floor vegetation data were obtained from 6 plots (1x1m2) in each growth forms and slopes. Water infiltration were analyzed using rain simulation method in 0.5x0.5m2 plot size. Results showed that there were 18 species of 5 families and 29 species of 10 families found during the dry and wet season respectively. Rainy season triggered grass and herbaceous (Poaceae and Asteraceae) plant density from 5 to 9 times, and also shrubs density from 3 to 6 times. Based on important value analysis at slope classes, Panicum repens (34.7%), Ischaemum sp. (34.2%), Elephantopus scaber (33.5%), and Desmodium triflorum (11.9%) are grasses and herbaceous dominated all slopes during both seasons. Boerhavia difussa, Chromolaena odorata, Flemingia macrophylla, and Mimosa pudica are shrubs dominated in all slopes, especially at the steep slopes for the last 3 shrubs.Â  The diversity index of the floor vegetation can be categorized low. Based on the rain simulation with average rate of 67.6 mLs-1, P. repens and M. pudica, can respectively withstand water runoff for 27s and 18s and had infiltration capacity of 83.2 % and 75.9 % in the steep slope, and E. Scaber can withstand water runoff for 15s and had infiltration capacity 71.6% in the gentle slope.